Levels of muscle activation in strength and conditioning exercises and dynamometer hiking in junior sailors - Burnett, A. F.; Wee, W. K.; Xie, W.; Oh, P. W.; Lim, J. J. H.; Tan, K. W. W. (The Journal of Strength and Conditioning Research, 2012)
Although strength and conditioning exercises have been prescribed to enhance performance and prevent injury in sailors, little is known about these exercises in comparison to the demands placed on the sailor's musculature while hiking maximally. Because of the difficulty in collecting hiking-related data on water, a 3-minute maximal hiking test (HM180) has been previously developed for use in the laboratory setting. There were 2 aims of this study. The first aim was to determine whether discriminative validity could be shown for the HM180 test in a group of junior sailors of differing ability level and gender. The second aim was to determine whether differences in muscle activation existed between selected strength and conditioning exercises and the HM180 test. Twenty-nine adolescent boy and girl sailors aged between 14 and 16 years from the Singaporean National Byte Class training squad (n = 12) and the Singapore High Participation Group (n = 17) were recruited for this study. The average levels of normalized muscle activation in selected lower limb and trunk muscles in 4 selected strength and conditioning exercises (leg extension, back squat, and back extension exercises, a 30-second hiking hold) and a maximal 3-minute hiking test (the HM180 test) were quantified. Discriminative validity of the HM180 test was shown, and it was confirmed that the strength and conditioning exercises provide an overload stimulus for the HM180 test. Further, similar levels of muscle activation were found for the vastus lateralis in the leg extension and back squat exercises, and the superficial lumbar multifidus in the back extension and back squat exercises. This study has the potential to inform the design of strength and conditioning programs for junior sailors.